Human papillomavirus infection and cancer development: virological and epidemiological aspects - Cavalcanti, Sílvia M.B.; Zardo, Lucília G.; Passos, Mauro R.L.; Oliveira, Ledy H.S. (Brazilian Journal of Sexually Transmitted Diseases, 1999)
A study was conducted to determine the prevalence of HPV infection in cervical lesions of Brazili-an women and to search for other Sexually Trans-mitted Diseases (STDs) associated with progression to malignancy. Five hundred and fourte en paraffinembedded biopsies obtained from female cervi-cal lesions were classified according to the Bethes da System in low grade squamous intraepithelial lesion (LSIL), high grade SIL (HSIL) and squamous cell carcinoma (SCC). Specimens were tested for the presence of human papillomavirus (HPV) types 6 / 11,16/ 18 and 31/33/35 DNA using non-isotopic in situ hybridization. HPV p revalence ranged from 85.6% in LSIL to 55.2 % in SCC. Patients were analysed through an eight-year period: 27 . 1 % of the lesions spontaneously regressed while 29.3% progressed to carcinoma. High risk types were present in 80.5% (OR 13.2, P=0.0003) of the progressive lesions. History of other sexually transmitted diseases, mainly syphilis, showed to be positively related to progression (OR 13.0, P = 0.0003). Oncogenic HPV types 16 and 18 and history of other Sexually Transmi tted Diseases showed to be significantly associa-ted to progression to cancer. Our study indicated that HPV and other STDs can act together, corroborating_ the observation of a poor prognosis for Brazilian women presenting SILs.